Mauritian tort law - Georgijević Goran (Anali Pravnog Fakulteta u Beogradu)
According to the general tort law of Mauritius (articles 1382 through 1384 of the Mauritian Civil Code), three conditions must be met before tort liability may be implemented, namely the existence of harm, the existence of a causal link, and the existence of a harmful event. This paper contains an analysis of the fundamentals of the tort law of Mauritius, which is based on Mauritian case law and French case law and French doctrine, which are considered a persuasive authority in Mauritian Civil Law.